THE RELATIONSHIP OF FEAR OF MISSING OUT (FoMO) AND PEER SOCIAL SUPPORT WITH THE BODY IMAGE OF FEMALE ADOLESCENT AT SENIOR HIGH SCHOOL - Marfita, Mayra Putri; Fitryasari, Rizki; Ni'mah, Lailatun (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2024)
Introduction: Adolescent girls are involved and exposed to various comments regarding physical appearance, which can lead to experiences of body dissatisfaction, resulting from failing to meet the unrealistic standards of physical attractiveness set by society. This condition can be influenced by FoMO and social support from peers. This research aims to analyze the relationship between Fear of Missing Out (FoMO) and social support from peers with body image in adolescent girls at SMA Negeri 13 Surabaya. Method: This research use descriptive correlation design with cross-sectional approach. The population was 650 people, with a sample size of 191 female teenagers at senior high school in Surabaya. The sampling technique used is simple random sampling. The independent variables are FoMO and peer social support. The dependent variable is body image. Data was taken using a questionnaire and analyzed using the Spearman's rank test. Results: There is a relationship between FoMO and body image in female adolescents (p=0,031<0.05 and (r) = -0,156). For the peer social support variable, the value obtained was p=0,568>0,05, which means there is no relationship. Discussion: FoMO may be related to body image. Peer social support is not associated with body